Ações em educação em saúde na educação básica: das percepções às práticas - Perdomo Junior, Joelio Dias (2024)
Health is a transversal theme that is integral to official curriculum documents. Understanding this topic is crucial, as it empowers students to make informed healthy choices, adopt positive attitudes, and engage in beneficial behaviors. This underscores the significance of health education initiatives within the school environment. Consequently, this study aimed to analyze the perceptions of students and teachers regarding the implementation of pedagogical actions focused on health education. Guided by action research, the participants included both students and teachers from the elementary school at Francisca Weinmann. The study stages were structured around the Problematization Methodology, utilizing the Maguerez Arch. Various methods were employed during the study, including semi-structured questionnaires, photographic records, and participant observation. The findings are presented in two manuscripts and two articles. The first manuscript resulted from an analysis of the curriculum in the city of Santa Maria/RS, while the second focused on investigating strategies to promote health based on the Problematization Methodology. One of the articles centers on teachers' perceptions of health education, and the other reflects students' views and interests regarding health. Upon concluding this research, it became evident that health-related themes are present in the municipal curriculum document, but are mainly confined to three components and approached in a reductionist and behaviorist manner. Both students' and teachers' perceptions highlight an understanding of health as multifactorial, with a unanimous assertion of the necessity to develop health education initiatives in the school environment. The Problematization Methodology proved to be a significant strategy for promoting health, fostering interaction and collaboration among students, teachers, professionals, and the broader school community. Furthermore, it contributed to the development of interdisciplinary practices, the exploration of new methodologies, and the establishment of valuable partnerships.